Pneumonia Severity Index in the Immunocompromised - Kevin M Sanders; Theodore K Marras; Charles KN Chan (Canadian Respiratory Journal)
BACKGROUND: The pneumonia severity index (PSI) accounts for many comorbidities, but not immunosuppression.